The role of gut microbiome in the complex relationship between respiratory tract infection and asthma - Zhao, Xiaoman; Hu, Mingge; Zhou, Huan; Yang, Yan; Shen, Shiping; You, Yannan; Xue, Zheng (Frontiers in Microbiology, 2023)
Asthma is one of the common chronic respiratory diseases in children, which poses a serious threat to children's quality of life. Respiratory infection is a risk factor for asthma. Compared with healthy children, children with early respiratory infections have a higher risk of asthma and an increased chance of developing severe asthma. Many clinical studies have confirmed the correlation between respiratory infections and the pathogenesis of asthma, but the underlying mechanism is still unclear. The gut microbiome is an important part of maintaining the body's immune homeostasis. The imbalance of the gut microbiome can affect the lung immune function, and then affect lung health and cause respiratory diseases. A large number of evidence supports that there is a bidirectional regulation between intestinal flora and respiratory tract infection, and both are significantly related to the development of asthma. The changes of intestinal microbial components and their metabolites in respiratory tract infection may affect the occurrence and development of asthma through the immune pathway. Based on the bridge role of gut microbiome between respiratory tract infection and the occurrence and development of asthma, this review summarizes the latest research progress of gut microbiome in the mechanism of respiratory tract infection in the induction and exacerbation of asthma, explores the role of gut microbiome in the induction and exacerbation of asthma by infection, and provides new ideas for further studying the mechanism of the relationship between respiratory tract infection and asthma.